Study of the Main Factors Affecting Heavy Soils and Measures Against Them - Khalimova Sh. R. (European Journal of Life Safety and Stability (2660-9630), 2022)
The work is devoted to methods for determining heaving soils when exposed to moisture. We know that during heaving in engineering structures, irregularities, cracks, and precipitation are formed. The development of heaving depends on the granulometric, mineralogical composition, on the rise in the level of groundwater. When exposed to moisture on soils and groundwater, we made an analysis of the indicators of heaving and measures against heaving in highways. Engineering structures, in order to serve for many years, it is necessary to take measures against the abysses.